Analisis Nilai Sosial dalam Pembelian Air Minum Dalam Kemasan BAQNU - Pambudi, Fajar; Purwanto, Purwanto; Labib, Achmad (Forum Kerjasama Pendidikan Tinggi, 2024)
This research analyzes the social value of purchasing BAQNU bottled drinking water. The qualitative research method focuses on an in-depth understanding of social values' influence on consumer purchasing decisions. The research results show that the social value in purchasing BAQNU brand bottled drinking water is not only limited to the consumptive aspect but also involves emotional and moral elements related to the identity and values ​​of certain social groups, especially Nahdlatul Ulama. Consumer purchasing decisions for BAQNU brand drinking water are influenced by familiarity with social groups, feelings of solidarity, and support for social programs carried out by these groups. These findings indicate that social value factors have a significant role in shaping consumer preferences and can strongly motivate the decision to purchase BAQNU bottled drinking water products. The implications of this research can provide valuable insight for marketers and companies in developing more targeted and social value-based marketing strategies to increase product attractiveness in the market.